Neferine Promotes GLUT4 Expression and Fusion With the Plasma Membrane to Induce Glucose Uptake in L6 Cells - Zhao, Ping; Tian, Di; Song, Guanjun; Ming, Qian; Liu, Jia; Shen, Jinhua; Liu, Qing-Hua; Yang, Xinzhou (Frontiers in Pharmacology, 2019)
Glucose transporter 4 (GLUT4) is involved in regulating glucose uptake in striated muscle, liver and adipose tissue. Neferine is a dibenzyl isoquinoline alkaloid derived from dietary lotus seeds and has multiple pharmacological effects. Therefore, this study investigated neferine’s role in glucose translocation to cell surface, glucose uptake and GLUT4 expression. In our study, neferine upregulated GLUT4 expression, induced GLUT4 plasma membrane fusion, increased intracellular Ca2+, promoted glucose uptake and alleviating insulin resistance in L6 cells. Furthermore, neferine significantly activated phosphorylation of AMP-activated protein kinase (AMPK) and protein kinase C (PKC). AMPK and PKC inhibitors blocked neferine-induced GLUT4 expression and increased intracellular Ca2+. While neferine-induced GLUT4 expression and intracellular Ca2+ were inhibited by G protein and PLC inhibitors, only intracellular Ca2+ was inhibited by inositol trisphosphate receptor (IP3R) inhibitors. Thus, neferine promoted GLUT4 expression via the G protein-PLC-PKC and AMPK pathways, inducing GLUT4 plasma membrane fusion and subsequent glucose uptake and increasing intracellular Ca2+ through the G protein-PLC-IP3-IP3R pathway. Treatment with 0 mM extracellular Ca2+ + Ca2+ chelator did not inhibit neferine-induced GLUT4 expression, but blocked neferine-induced GLUT4 plasma membrane fusion and glucose uptake, suggesting the latter two are Ca2+-dependent. Therefore, we conclude that neferine is a potential treatment for type 2 diabetes.